Potensi Wisata Bahari dan Budaya Suku Sampan dalam Mendukung Pariwisata Berkelanjuta di Kampung Panglong Kabupaten Bintan - Indah Andesta; Hendrikus Andre; Miranti Miranti (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Panglong Village, Berakit Subdistrict, Bintan Regency, possesses significant potential for development within the sustainable tourism sector. This study aims to investigate the marine and cultural potentials of the Sampan ethnic community in supporting sustainable tourism development in Panglong Village. The analysis employs a qualitative descriptive approach, guided by the 4A framework, encompassing Attraction, Accessibility, Amenities, and Ancillary Services. The findings indicate that Panglong Village offers compelling tourism attractions from both marine and cultural perspectives; however, its management remains limited and has yet to be optimally implemented. The marine potential is closely linked to the mangrove ecosystems, which can be leveraged as attractions through mangrove tourism tours, traditional fishing activities, and the rich cultural heritage of the Sampan community. Achieving sustainable development in this context necessitates effective collaboration among local communities, academics, government authorities, and industry stakeholders to safeguard natural and cultural resources. Furthermore, to realize this potential fully, improvements in accessibility, tourism facilities, and supporting services are essential to ensure sustainable tourism that prioritizes visitor safety and comfort.